Use of Chimney Technique Does Not Improve the Outcome of Endovascular Aneurysm Repair in Patients With a Hyperangulated and Short Proximal Aortic Neck. (June 2022) - Özdemir-van Brunschot, Denise Michelle Daniëlle; Torsello, Giovanni Battista; Bernardini, Giulia; Litterscheid, Sarah; Torsello, Giovanni Federico; Beropoulis, Efthymios
Purpose: We hypothesized that extending the proximal landing zone with the chimney technique could be beneficial in patients with a hyperangulated proximal aortic neck, defined as more > 60 degrees. Material and Methods: We retrospectively analyzed the outcome of prospectively collected data of patients treated by endovascular aneurysm repair (EVAR) for infrarenal aortic aneurysm with a hyperangulated proximal aortic neck. In all, 104 out of 130 patients were treated without (Group A) and 24 with the chimney endovascular aortic repair (ChEVAR, Group B). Primary outcome was technical and clinical success according to the reporting standards of the Society of Vascular Surgery. Results: The use of the chimney technique was associated with a significantly longer operation duration (167 vs. 93 min, p < .001), longer fluoroscopy time (44 vs.30 min, p = < .001), and larger amount of contrast medium used (149 vs. 127 ml, p = .03) but did not significantly improve technical (79.2% vs. 87.7%) and clinical success (54.2% vs. 68.9%). Aneurysm-related mortality was higher in group B (8.3% vs. = 0%, p < .001). Type IA endoleak was high in both groups at completion angiography (11.3% in Group A vs. 12.5% in Group B) and at follow-up (10.4% in Group A vs. 4.5% in Group B) without significant difference between the groups. Conclusions: Our data did not show a benefit of the primary use of the chimney technique in patients with a hyperangulated and short neck, although more studies are required to support this conclusion. Other strategies or new technologies are required for improving EVAR results in aneurysm patients with severe angulated proximal and short neck.